Diagnosis of bovine rotavirus: an overview of currently available methods - Huang, Ying; Li, Zhi; Fu, Yong; Wang, Shu Qin; Kang, Ming; Meng, Ru (Frontiers in Microbiology, 2025)
Bovine rotavirus (BRV) is a significant pathogen that causes diarrhea in calves, profoundly impacting the cattle industry and resulting in substantial economic losses. Currently, the established diagnostic approaches for BRV primarily include etiological methods, such as electron microscopy, virus isolation, and culture; serological methods, including enzyme-linked immunosorbent assay (ELISA), latex agglutination test (LAT), and immunofluorescence techniques; and molecular biological methods, such as reverse transcription-polymerase chain reaction (RT-PCR), real-time quantitative PCR (qPCR), and loop-mediated isothermal amplification (LAMP), as well as next-generation sequencing (NGS) technology. This review summarizes the current diagnostic methods for BRV, discusses their advantages and disadvantages, and presents future perspectives on BRV diagnosis, aiming to provide valuable references for the effective diagnosis and control of BRV-related diseases.